'We know our Terrain': indigenous knowledge preferred to scientific systems of weather forecasting in the Delta State of Nigeria. (7th February 2019) - Ebhuoma, Eromose E.; Simatele, Danny M.
Abstract : It is acknowledged that subsistence farmers in developing countries rely on indigenous knowledge systems (IKS) to determine the appropriate time, the types and quantity of food to produce in a particular farming season. Due to the unprecedented rate in which climate variability is occurring globally, there are concerns that IKS will become unreliable to predict future weather events accurately, which will compromise the ability for farmers to secure their livelihoods. Nonetheless, some scholars are optimistic that if farmers rely on seasonal climate forecast (SCF), it will facilitate the adoption of planned and more efficient adaptation strategies, thereby ensuring that they continue effectively in food production. While most countries in sub-Saharan Africa have been investing in meteorology, farmers still rely heavily on IKS. Drawing on fieldwork conducted in the Delta State of Nigeria, this paper discusses the factors that contribute towards farmer's willingness to adhere to IKS. The results suggest that being misled by an inaccurate scientific forecast, and the inability to comprehend how anthropogenic activities contribute to climate change, among others, have contributed to the farmer's continued reliance on IKS. These issues have been explored within the broader contemporary theoretical arguments and debates revolving around IKS and SCF.